DETERGENT AIDED REFOLDING AND PURIFICATION OF RECOMBINANT XIAP FROM INCLUSION BODIES - NAGY, Katalin; KOVÁCS, Zita; MIKLÓSSY, Ildikó; SALAMON, Pál; ORBÁN, Csongor-Kálmán; ALBERT, Beáta; LÁNYI, Szabolcs (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Human proteins expressed in prokaryotic systems tend to form inclusion bodies. Proteins in inclusion bodies are inactive and the refolding of these densely packed protein molecules is affected by several factors depending on the applied refolding technique. To obtain the active form of protein the most common technique is denaturation of the protein aggregates followed by refolding of inclusion proteins. Conventional denaturants for solubilization are urea, guanidine hydrochloride and sodium dodecyl sulphate (SDS), while refolding can be achieved by several techniques found in the literature. In our study, the recombinant GST-tagged XIAP (X-linked Inhibitor of Apoptosis protein) construct was expressed as inclusion bodies. The protein was solubilized with high efficiency using N-Lauroylsarcosine (ionic detergent). A chromatography-based method using different ratios of detergents was investigated for the refolding process. Batch mode affinity purification was successfully executed using Glutathione Sepharose 4B resin and TritonX-100, n-octyl β-D-thio-glucopyranoside (OTG) and 3-[(3-cholamidopropyl) dimethylammonio]-1-propanesulfonate hydrate (CHAPS) detergents in the appropriate ratio. Finally, the refolded protein was purified by size-exclusion chromatography and investigated by western blot analysis.